PENGEMBANGAN MODUL BERORIENTASI CONTEXTUAL TEACHING AND LEARNING (CTL) DILENGKAPI PETA PIKIRAN PADA MATERI SISTEM DALAM KEHIDUPAN TUMBUHAN KELAS VIII SMP - Rahim, Cici; Syukur, Ulfa; Lufri, Lufri (Kolaboratif, 2014)
Biology is one of the subjects that requires skills and students’ understanding of concepts related to natural surroundings. In biology, subjects are required in to develop their potentials in finding the concepts in the subject matter. The teacher as facilitator of learning is responsible for the provision of instructional media in the form of teaching materials that will be used by students. The instructional materials used must be in accordance with the needs and characteristics of the students as well as to provide convenience for students in studying learning materials. One effort that can be done is by the use of contextual teaching and learning with mind maps on the system in plant life topics for students in grade viii of junior high school. The module is an instructional materials that contain materials in a systematic and purposeful that the modules can lead students to be able to learn independently. This research aims to produce a module-oriented contextual teaching and learning equipped with valid, practical and effective mind map. This type of research is the development of research. The model and the procedure of development uses 4D models comprising the step of define, design, develop. Data collection instruments used in this research is the validation module sheet, questionnaire practicalities for teachers and students,  effectiveness, student activities and student learning out comes of cognitive, affective and psychomotor. The design of the module has been designed and validated by experts and practitioners later in the trial limited to the class VIII2 of SMPN 22 Padang. The results showed that the modules developed are very valid, very practical and very effective. The average value of validation module if 86.7%, the average value of the practicalities is 90.4%; the testing of the effectiveness of the module can be seen from the students’ activities and students’ competencies. It can be concluded that the module oriented the contextual teaching and learning equipped mind maps on the material systems plant life for junior high school grade VIII is valid, practical and effective.